Kerr-Raman Optical Frequency Combs in Silica Microsphere Pumped Near Zero Dispersion Wavelength - Elena A. Anashkina; Alexey V. Andrianov (IEEE Access, 2021)
Optical frequency combs generated in whispering gallery mode microresonators are in high demand for basic science and a large number of applications including telecommunication systems and quantum optics. Here, we study experimentally and theoretically optical frequency comb generation in a silica microsphere with a zero dispersion wavelength near $1.55 μm pumped by a continuous wave laser widely tunable in the C-band. We considered the optical frequency comb generation for a pump wavelength in a normal dispersion region, in a low anomalous dispersion region, and very close to the zero dispersion wavelength. Kerr-assisted and Raman-assisted (Stokes) combs as well as anti-Stokes combs emerging due to the four-wave mixing between the Kerr and Raman combs are attained in experiments. The mechanisms of producing individual peaks of optical frequency combs are verified in numerical simulations. A 270-nm optical frequency comb covering the telecommunication E-, S-, C-, L-, U-bands and further up to $1.7 μm is also demonstrated.